If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5 = 5x + -22 Reorder the terms: 5 + 2x = 5x + -22 Reorder the terms: 5 + 2x = -22 + 5x Solving 5 + 2x = -22 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 5 + 2x + -5x = -22 + 5x + -5x Combine like terms: 2x + -5x = -3x 5 + -3x = -22 + 5x + -5x Combine like terms: 5x + -5x = 0 5 + -3x = -22 + 0 5 + -3x = -22 Add '-5' to each side of the equation. 5 + -5 + -3x = -22 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = -22 + -5 -3x = -22 + -5 Combine like terms: -22 + -5 = -27 -3x = -27 Divide each side by '-3'. x = 9 Simplifying x = 9
| 6x+4y=20 | | 16q+2q-18q+3q-q=16 | | (4a+5)(a+7)=0 | | 21=48-36x | | 18-2/5x=-22 | | -2x-28=7(x+5) | | -20=4-4x-6x | | 8x+8+4x=5x+20+5x | | y=3x^2+6x-17 | | 84-4b^2=0 | | (13.5+13.25)*X=35.67 | | -6(u-9)=-4u+44 | | (2x^4/3)^3 | | 3p^5-2/18pm^5 | | 21-12x-1=24-4x+3x | | 13.5+13.25*x=35.67 | | x/x=42/12 | | 3y+37=-2(y-6) | | 123=3x^2 | | 6x/2−8x/1=2 | | 5x+7+2=12+3-3x | | 8x-1=9x-2 | | -3y+37=-2(y-6) | | 25p^2-16= | | x/26.75=35.67 | | 3s+10=5s+3 | | y=-6+34 | | 13x+7=16x-4 | | -2(w+8)=-5w-43 | | y=8x-128 | | 26.75*x=35.67 | | b-3/5=-1 |